2020
DOI: 10.1007/s10571-019-00744-x
|View full text |Cite
|
Sign up to set email alerts
|

The Angiotensin Type 1 Receptor Antagonist Losartan Prevents Ovariectomy-Induced Cognitive Dysfunction and Anxiety-Like Behavior in Long Evans Rats

Abstract: Women who have bilateral oophorectomies prior to the age of natural menopause are at increased risk of developing mild cognitive decline, dementia, anxiety, and depressive type disorders. Clinical and animal studies indicate angiotensin type 1 receptor (AT 1 R) blockers (ARBs) have blood pressure (BP)-independent neuroprotective effects. To investigate the potential use of ARBs in normotensive women at increased risk of developing neurocognitive problems, we studied a rat model of bilateral oophorectomy. Long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 81 publications
3
17
0
Order By: Relevance
“…Taken together, these outcomes raise the question whether the observed effects also apply to other drugs acting on RAS. The AT1R antagonist losartan was able to relieve ovariectomy-induced increase in anxiety-like behavior in the elevated plus-maze, and cognitive impairment in the novel object recognition test, and decreased the levels of plasma corticosterone [42]. Telmisartan, another AT1R antagonist, reduced the consequences of stress on cognitive impairment, and inhibited the activity of the HPA axis [43].…”
Section: Discussionmentioning
confidence: 98%
“…Taken together, these outcomes raise the question whether the observed effects also apply to other drugs acting on RAS. The AT1R antagonist losartan was able to relieve ovariectomy-induced increase in anxiety-like behavior in the elevated plus-maze, and cognitive impairment in the novel object recognition test, and decreased the levels of plasma corticosterone [42]. Telmisartan, another AT1R antagonist, reduced the consequences of stress on cognitive impairment, and inhibited the activity of the HPA axis [43].…”
Section: Discussionmentioning
confidence: 98%
“…There is some evidence indicating that ovariectomy in youngadult females has anxiogenic effect (16)(17)(18)(19)(20). However, there is little data on the effect of ovariectomy on anxiety in middleaged rats (44).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have shown that ovariectomy may induce cognitive dysfunction in young ( 13 16 ) and also in middle-aged rats ( 29 , 30 , 43 ), while estrogens may improve learning and memory performance following ovariectomy in both, young ( 15 , 24 , 59 61 ) and middle-aged females ( 21 23 , 25 , 29 , 31 ). However, OVX females in our experiment exhibited mild memory impairment only, and the estradiol-treated group did not outperform vehicle-treated OVX rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations